Sharing semangat taqwa: social media and digital Islamic socialities in Bandung. Issue 134 (2nd January 2018) - Lengauer, Dayana
ABSTRACT: Bandung is home to numerous groups or so called komunitas who effectively seize emerging social spaces evolving from the interplay between urban and technological development and the increased use of social media in all spheres of everyday life, including religious practice. Based on ethnographic online and offline research among Muslim groups, this article enquires into contemporary expressions of piety ( taqwa ) and the formation of pious Muslims selves across online and offline spheres of interaction. As part of daily practice, social media become sites of digital Islamic socialities that distinguish these Muslim groups from other Islamic movements or religious associations. Beyond the purpose of communication, social media enhance forms of affective awareness and exchange required for the integration of multiple and transient relations. Building on insights from anthropological research on the Internet and the use of digital technologies in Indonesia and beyond, this article shows how social media affect the experience and understandings of personal commitment and social engagement that define contemporary Muslim subjectivities. Embedded in the cyberurban space of Bandung, emerging (digital) Islamic socialities offer new orientations and models of sharing the 'zeal of piety' ( semangat taqwa ) that are appealing and easily adopted by a young generation of pious Muslims.